أنتاج الفقر في الدول النامية بين المفهوم والأسباب - صالح لورنس يحيى; محمد اسماء جاسم (Journal of Economics and Administrative Sciences, 2010)
The poverty in the developing countries is output to under development as we consider welfare, where as when the poverty disappear that produced be the general development . Historically, in our countries, the underdevelopment is the result of colonialism period and what is associated with it of transferring the surplus abroad and the disorder of production structure. And at the present time, the poverty is reproduced and aggravated in the last years as a result of many internal and external reasons.Today, poverty is associated in many forms with the poverty previously. المقدمة